A comparative study of the management decisions by IMNCI algorithm and by pediatricians of a teaching hospital for the children between 2 months to 5 years - Agnihotri Bhattacharyya; Chitra Chatterjee; Sukanta Chatterjee; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2012)
Background: Integrated management of neonatal and childhood illness (IMNCI) is already operational in many states of India, but there are very few studies in Indian scenario comparing its validity and reliability with the pediatricians' decisions. Objectives: 1) To compare the IMNCI decision with the decision of pediatricians; 2) to assess the significance of multiple presenting symptoms in the IMNCI algorithm. Materials and Methods : The study was conducted among the sick children between 2 months to 5 years presented in pediatric department from January to March 2009. The IMNCI decision was compared with pediatrician's decisions by percent agreement, Kappa and weighted Kappa with the aids of SPSS version 10. Results: The overall diagnostic agreement between IMNCI algorithm and pediatrician's decisions was 36.64%, (Kappa 0.16 and weighted Kappa 0.29) with 51.15% over diagnosis and 12.21% under diagnosis. The importance given by IMNCI algorithm in cases of multiple presenting symptoms was also reflected as it was evident that 37.50% children presented with three symptoms were categorized as red, whereas it was 28.57% and 11.67% for those presented with two and one symptom, respectively, (P < 0.0001). Pediatricians also gave importance for presence of multiple symptoms by considering 50% as admissible in the group presented with three symptoms, 30.16% in the group presented with two symptoms, and 16.67% in the group presented with only one symptom. The association was also statistically significant (P = 0.018). Conclusion: Diagnostic discordance is seen mainly due to over diagnosis of all fever cases as malaria. Importance of presence of comorbidities was also reflected.